Evaluation of the efficacy of Debaryomyces hansenii as protective culture for controlling Listeria monocytogenes in sliced dry-cured ham. (February 2020) - Alía, Alberto; Córdoba, Juan J.; Rodríguez, Alicia; García, Carmen; Andrade, María J.
Abstract: The anti- Listeria monocytogenes activity of 30 Debaryomyces hansenii strains was evaluated to be used as protective cultures in sliced dry-cured ham. Some of the yeast strains exhibited inhibitory potential against the L. monocytogenes strains S2, S4-2, S12-1 and S7-2 belonging to the serotypes 1/2a, 1/2b, 1/2c and 4b, respectively, when they were co-inoculated in a dry-cured ham-based medium at 0.95 and 0.93 water activity (aw ). The antagonistic activity varied with the yeast and bacterium strains and the aw . The most active strain ( D. hansenii 258H) was selected for assessing its activity on slices of dry-cured ham. D. hansenii 258H showed a limited action and even a promotion of the L. monocytogenes growth in the slices of dry-cured ham. In addition, the upregulation of some key virulence genes of L. monocytogenes and the unsuitability appearance on the slices of dry-cured ham inoculated with D. hansenii 258H suggest that such yeast is not a good candidate to be used as protective culture against L. monocytogenes in sliced dry-cured ham. Such effect should be considered even if D. hansenii is not used as a protective culture due to its presence as native microbial population in dry-cured ham. Highlights: A minority of yeasts inhibited L. monocytogenes in a dry-cured ham-based medium. The antagonistic effect of yeasts was L. monocytogenes strain and aw dependent. D. hansenii 258H affected relative expression of L. monocytogenes virulence genes. D. hansenii 258H affected the visual acceptance of inoculated dry-cured ham slices.